An Analysis of Students Anxiety in Speaking English at Senior High School - Muhammad Wahidul Quthbi, Naufal (RETAIN : Journal of Research in English Language Teaching, 2023)
The purpose of the study analysis was to discover the factors of students' anxiety in speaking English. This study was conducted with 25 students from the twelfth grade of senior high school 2 Ponorogo using a mixed method research design. As data sources, an observation, a questionnaire, and a semi-structured interview were employed. Observation, questionnaires, and interviews are used to collect data for the study. To examine the data, the acquired data from questionnaires and interviews were processed, analyzed, coded, and interpreted. It found that most of students feel anxiety about speaking English. However, the speaking’s anxiety is existence in students when they are speaking English. The factors that contributed in students’ speaking anxieties are communication apprehension, test anxiety, and fear of negative evaluation. It is recommended for EFL teachers to identify students' anxiety in speaking and improve their speaking skills.